2016
DOI: 10.3945/ajcn.115.120824
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional association between parental child-feeding practices and body mass index at 4 and 7 y of age

Abstract: Background: Evidence of the association between parental childfeeding practices and the child's body mass index (BMI) is controversial, and bidirectional effects have been poorly studied. Objective: We aimed to examine bidirectional associations between parental child-feeding practices and BMI at 4 and 7 y of age. Design: This study included 3708 singleton children from the Generation XXI birth cohort with data on parental child-feeding practices and BMI at 4 and 7 y old. Feeding practices were assessed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
99
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 35 publications
20
99
2
3
Order By: Relevance
“…Apparently, mothers are sensitive to their child's weight status and adapt their feeding practices accordingly, probably with the intention to reduce children's food intake and improve health and well-being (29). This result is in line with results from a Portuguese longitudinal study (28) and also corresponds with research on other controlling feeding practices, which showed that parents use more coercive feeding strategies when their child is very thin (27,35).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Apparently, mothers are sensitive to their child's weight status and adapt their feeding practices accordingly, probably with the intention to reduce children's food intake and improve health and well-being (29). This result is in line with results from a Portuguese longitudinal study (28) and also corresponds with research on other controlling feeding practices, which showed that parents use more coercive feeding strategies when their child is very thin (27,35).…”
Section: Discussionsupporting
confidence: 84%
“…However, this hypothesis was examined only a few times with contradictory findings. A longitudinal study in a UK cohort found no evidence for this hypothesis (12), whereas in the Dutch Generation R and Portuguese Generation XXI cohorts, associations between child weight and later restriction were found (27,28). It can be speculated that parental concern about children becoming overweight might drive the restriction of children's food intake.…”
Section: Introductionmentioning
confidence: 99%
“…These findings along with the significant relationship found between pressure-to-eat and both current and birth weight, also provides evidence earlier than previously reported, 172,173 that this controlling feeding practice may be influenced by, as well as having an impact on, weight status, reinforcing the need to address weight expectations.…”
Section: Discussionsupporting
confidence: 70%
“…23,166,170,171 Current longitudinal evidence now supports the bidirectional relationship between these feeding practices and child weight, with a few large studies suggesting that feeding practice adaption in response to child's weight as the dominant direction. 172,173 If infant weight status is a driver of inappropriate feeding practices, then parental perceptions of their child's weight and identification of healthy weight is important.…”
Section: Feeding Practicesmentioning
confidence: 99%
“…Research focused on growth and human developments [4][5][6][7] has been highlighted and since its establishment in the 1990s it has been the central theme of this Journal. In the current issue of JHGD these studies evaluate technologies that involve the improvement of health conditions and/or issues for public health investigating the health situation of the population, especially children and adolescents [8][9][10] , which corroborate the themes in the health promotion field within the context of primary care focusing on teens and their vulnerabilities [11][12][13] , nutrition and influence on child and adolescent development [14][15][16][17][18] and themes focused on translational medicine, describing results to improve the health indicators of the population [19][20][21][22] .…”
mentioning
confidence: 99%